Bcl‐2 family in non‐small cell lung cancer: its prognostic and therapeutic implications. Issue 3 (19th January 2017) - Sun, Ping‐Li; Sasano, Hironobu; Gao, Hongwen
Abstract : Non‐small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancers. Despite significant advances in its research of tumor biology and therapy, the prognosis for this neoplasm has still remained poor. The great majority of anticancer agents, regardless of their mechanisms of action, exert their lethal actions on cancer cells by inducing apoptosis following drug‐induced cellular damage. Many reported studies have evaluated the prognostic and therapeutic implications of apoptosis in lung cancer, but their exact clinical value has remained unclear. Therefore more prospective studies are currently required to further validate apoptosis as prognostic and predictive biomarkers in lung cancer patients. The current study reviewed the studies on the prognostic and predictive significances of Bcl‐2 family proteins in NSCLC. We also discussed potential treatment strategies which could target apoptotic proteins in lung carcinoma cells. Exception for Bcl‐2 itself, studies of the prognostic significance of other Bcl‐2 family proteins is markedly limited. The abundance of literature suggests that targeting apoptosis in NSCLC is feasible. However, many troubling questions arise with the use of new drugs or treatment strategies, and new biomarkers are needed.